Enhancement in fatigue life of Ti-13Nb-13Zr alloy through ultrasonic shot peening - Kumar P.; Mahobia G.S.; Chattopadhyay K. (My University, 2025)
β-Ti (Ti–13Nb–13Zr) alloy was subjected to ultrasonic shotpeening (USSP) and a nanocrystalline layer of ~60 µm thickness was developed on the metastable Ti-13-Nb-13Zr alloy. In this investigation, the surface hardening and low cycle fatigue (LCF) behavior of the alloy were studied after USSP treatment. Compared to the un-shotpeened samples, the shotpeened specimens exhibit high surface hardness and an enhancement in fatigue life. A notable impact of USSP on the fatigue crack initiation and growth of the alloy was also observed. The results show that the crack initiation at free-surface was suppressed due to the formation of a nanograined microstructure and fatigue crack initiation site shifts from surface to inside of the material. Further, the microstructural analysis proves that the nanograin formation and compressive stresses imparted by ultrasonic shot peening treatment are helpful in significant improvement of fatigue life. © 2019 Trans Tech Publications Ltd, Switzerland.